2021
DOI: 10.1021/acsnano.0c06528
|View full text |Cite|
|
Sign up to set email alerts
|

Polyelemental Nanoparticles as Catalysts for a Li–O2 Battery

Abstract: The development of highly efficient catalysts in the cathodes of rechargeable Li−O 2 batteries is a considerable challenge. Polyelemental catalysts consisting of two or more kinds of hybridized catalysts are particularly interesting because the combination of the electrochemical properties of each catalyst component can significantly facilitate oxygen evolution and oxygen reduction reactions. Despite the recent advances that have been made in this field, the number of elements in the catalysts has been largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The reliability and generalizability of the technique have facilitated the synthesis of other HEA nanoparticles comprising various combinations of elements. [ 114 , 115 , 116 , 117 , 118 ]…”
Section: Synthetic Methods For Various Nmmnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and generalizability of the technique have facilitated the synthesis of other HEA nanoparticles comprising various combinations of elements. [ 114 , 115 , 116 , 117 , 118 ]…”
Section: Synthetic Methods For Various Nmmnsmentioning
confidence: 99%
“…The reliability and generalizability of the technique have facilitated the synthesis of other HEA nanoparticles comprising various combinations of elements. [114][115][116][117][118] Lu and co-workers suggested that pyrolysis using a fastmoving bed is a reliable synthetic method for synthesizing HEA nanoparticles on granular supports (Figure 8b). [119] In this method, a boat containing precursor-loaded support was moved into the center of the furnace preheated to 923 K with a propulsion speed of ≈20 cm•s −1 .…”
Section: High Entropy Alloysmentioning
confidence: 99%
“…Third, the direct incorporation of nonmetallic components (e.g., carbon) into the metal active sites introduces serious complexity in terms of reliable calculations, although studies have reported that encapsulating graphene layers contribute to the catalytic performance. [35,36] Finally, computational calculations of multi-metallic unit cells are expensive owing to the necessity of large unit cells and the extensive requirement for k-vectors in the reciprocal space. As a result, errors from these uncertainties propagate through the computational process and introduce significant bias and epistemic uncertainty in the modeling; hence, the current metallic catalyst databases and ML techniques are not suitable for the universal exploration of multi-metallic alloy catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The time during which the temperature rises and falls is very short, and so it is a very innovative way of mixing multiple metals with small and uniform NPs (1). The ability to synthesize a desired NP can open exciting new possibilities for studying polyelemental NPs, and this method has already enabled notable applications such as rechargeable energy storage systems (e.g., Li and Na ion batteries, supercapacitors, and Li-CO 2 and Li-O 2 batteries), electrochemical water splitting (e.g., oxygen evolution reaction), and electrocatalysis (e.g., hydrogen evolution, oxygen reduction, and carbon monoxide reduction reactions) (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%